Uma historiografia do tempo presente entre as práticas pedagógicas de Matemática e a avaliação externa do SPAECE numa escola de educação básica no Ceará - Sousa, Robert David Fernandes de (2023)
This work is centred by the interfaces of the History of Mathematics Education (HEM) and presents a historiography of the present time on the pedagogical practices of Mathematics in a Basic Education school in the State of Ceará (CE) and the external evaluation of the Permanent System of Evaluation of Basic Education of Ceará (SPAECE). Thus, this whole thematic is distinguished by the following questions: Which Mathematics teaching practices are present in this school? Do SPAECE results influence the organisation of the work of mathematics teachers? Does the SPAECE evaluation process interfere in the teaching of mathematics? To answer these and other questions, the general objective of this work is to make a historiographic record of the relationships between the teaching practices of teachers who teach Mathematics and the SPAECE external evaluation on a large scale. The specific objectives are: to verify which are the existing Mathematics teaching practices through observation and listening of teachers who are inserted in the classroom context; to publicize these practices and understand the place of educational public policies of evaluative monitoring and; discuss the teaching of Mathematics in the face of external evaluations on a large scale. This research has a qualitative character and, as a methodological research strategy, we used bibliographic research, participatory observation and semi-structured interviews. Some teachers who teach Mathematics in this school were interviewed. As results, presence of an intense agenda of external assessments on a large scale within the school and that this model is culturally established, and that the main teaching tool for preparing students for these assessments is to simulate previous exams, and that although the external evaluation favors a direction, it ends up inducing teachers to develop a mathematics curriculum that is aligned to the matrices of this assessment, in addition to holding these agents responsible for the success and/or failure generating a "climate of tension", still in view of this record we realize that many of the practices are reproduced hereditarily. One of the requirements for who makes Professional Master is the development of an Educational Product (EP), we opted for the elaboration of a Guide of Elaboration/Use of Didactic Sequences: conciliating demands of Mathematics teaching and that in its core we present some discussions about these demands and, we present as a suggestion of methodology and application of a Didactic Sequence (SD) aimed at students of Primary Schools final years, about equations of the second degree and that includes some interactive digital activities.